Permafrost thaw affects boreal deciduous plant transpiration through increased soil water, deeper thaw, and warmer soils. Issue 3 (13th August 2013) - Cable, Jessica M.; Ogle, Kiona; Bolton, W. Robert; Bentley, Lisa P.; Romanovsky, Vladimir; Iwata, Hiroki; Harazono, Yoshinobu; Welker, Jeffrey
ABSTRACT The effect of thawing permafrost on boreal ecosystem water cycling represents a significant knowledge gap of how climate change will affect northern landscapes. Evapotranspiration, particularly transpiration, may be changing in response to changes in permafrost conditions, vegetation, and climate. This study focuses on the effect of permafrost thaw on boreal plant transpiration over two summers with contrasting weather conditions. We quantified the response of stomatal conductance (gs), from which transpiration was calculated, of deciduous and evergreen plants to soil environmental factors that permafrost thaw affects: soil water content (S), depth of seasonal thaw (D), and soil temperature (T). We found that gs was least sensitive to T compared with S and D at both sites and across both years. At the thawing site, gs was more sensitive to S in a dry year (2009) and to D in a wet year (2010). In the wet year, S of 50 cm represented a threshold wherein the sensitivity of gs to T and D switched between positive (S < 50 cm) and negative (S > 50 cm). However, the sensitivities to T and D were negative when S was consistently less than 50 cm in the dry year. This is one of the first studies to explore the effect of permafrost thaw on boreal plant gs and transpiration, and our model predicted higher transpiration rates from deciduous plants located on thawing permafrost. Copyright © 2013 John Wiley & Sons, Ltd.